2011
DOI: 10.1007/s10646-011-0831-x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular cloning and mRNA expression of the vitellogenin and nuclear receptor gene induced by 17β-estradiol in the mud carp, Cirrhinus molitorella

Abstract: Vitellogenins (VTGs), the precursors of yolk proteins, are crucial for the embryonic development of teleosts, and have also been studied extensively as biomarkers for environmental estrogenic mimics. The cDNA of a VTG was isolated from the liver of male mud carp (Cirrhinus molitorella) following induction by 17β-estradiol (E(2)) using 3'- and 5'-RACE methods. It was 4,216 bp in length, and encoded a putative protein of 1,342 amino acids. This putative VTG contained complete portions of lipovitellin I (LVI) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…The up-regulation of era and vtg mRNA levels was observed in all treatment groups after 20 and 40 days of exposure in the livers. It is reported that the expression of era and vtg demonstrated a significant relationship after E2 exposure in the liver of mud carp [45]. In female zebrafish, the increase of plasma E2 was accompanied by up-regulated hepatic era and vtg expression after exposure to fluorotelomer alcohol (6:2 FTOH) [46].…”
Section: Discussionmentioning
confidence: 99%
“…The up-regulation of era and vtg mRNA levels was observed in all treatment groups after 20 and 40 days of exposure in the livers. It is reported that the expression of era and vtg demonstrated a significant relationship after E2 exposure in the liver of mud carp [45]. In female zebrafish, the increase of plasma E2 was accompanied by up-regulated hepatic era and vtg expression after exposure to fluorotelomer alcohol (6:2 FTOH) [46].…”
Section: Discussionmentioning
confidence: 99%
“…However, the effects of E2 or EE2 on Ru-Vg gene expression are significantly lower compared to those seen in other fish. In fish such as the slender bitterling, mud carp, zebrafish, and rainbow trout, the levels of hepatocyte Vg mRNA or plasma Vg were induced on a logarithmic scale by E2 or EE2 treatments [42,43,44,45]. In contrast, VgAo1 mRNA levels in the hepatocytes of zebrafish and white cloud mountain minnow were only induced approximately 1.5- and 10-fold by E2 treatment [34,36].…”
Section: Resultsmentioning
confidence: 99%
“…As shown Figure 6, the 5'-flanking region of Ru-Vg was activated by the expression of ERα, and this expression was synergistically increased by ERα together with 10 –7 M E2 or 10 –7 M EE2. These results suggest that Ru-Vg expression can be regulated by estrogen derivatives and indicate that R. uyekii and the Ru-Vg gene may have utility as biomarkers for exposure to endocrine-disrupting chemicals (EDCs), which can be harmful to human health by disrupting the endocrine, reproductive, and immune systems [42,48]. …”
Section: Resultsmentioning
confidence: 99%
“…In this study, we did not find any other cDNA encoding other types of Vtg. To date, a single vtg form has been also found in another cyprinid species, C. molitorella (Liang & Fang, 2012). Miracle et al (2006) found that vtg1 induction levels in male fathead minnow (P. promelas)…”
Section: Discussionmentioning
confidence: 96%